2016
DOI: 10.1002/ldr.2629
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Sediment Connectivity Through man‐Made and Natural Sediment Sinks in the Minizr Catchment, Northwest Ethiopia

Abstract: Man‐made and natural sediment sinks provide a practical means for reducing downstream reservoir sedimentation by decreasing soil erosion and enhancing the rate of sedimentation within a catchment. The Minizr catchment (20 km2) in the northwest Ethiopian highlands contains numerous man‐made soil and water conservation (SWC) structures such as soil bunds (Erken), fanya juu ridge (Cab) and micro‐trenches and natural sediment sinks such as wetlands, floodplains and grassed waterways. These sediment sinks reduce do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 55 publications
3
49
0
Order By: Relevance
“…However, these methods are usually applied for periods, lasting up to a few years at most (Mekonnen et al, 2017;Masselink et al, 2017a,b). Further, they introduce artefacts into the pedological system which can affect the soil and possibly impact measurement quality.…”
Section: Comparisonmentioning
confidence: 99%
“…However, these methods are usually applied for periods, lasting up to a few years at most (Mekonnen et al, 2017;Masselink et al, 2017a,b). Further, they introduce artefacts into the pedological system which can affect the soil and possibly impact measurement quality.…”
Section: Comparisonmentioning
confidence: 99%
“…In the context of water-caused soil erosion, removal of soil particles is the result of raindrops, while surface runoff carried out the transportation process [4]. Though soil erosions are the result of the interplay between soil erodibility and rainfall erosivity factors, inappropriate human practices such as cultivation in upslope areas, deforestation, an extension of urban areas and roads, and uncontrolled and overgrazing aggravate the problem [5][6][7][8]. In connection to this, Knapen et al [9], reported that Israel [70] reported the mean annual soil loss rate of 58.30 t ha −1 y −1 and recommended the implementation of conservation measures to reduce the on-site and off-site effects of soil erosion in the Dire Dam Watershed.…”
Section: Introductionmentioning
confidence: 99%
“…Much has been written in geomorphology on the subject of sediment connectivity in its various forms, and has been extensively reviewed and critiqued (Bracken et al, 2015;Brierley et al, 2006;Fryirs, 2013;Wohl, 2017). Furthermore, there has been a profusion of geomorphic research addressing sediment connectivity to better understand sediment transfers at differing scales in the catchment sediment cascade (e.g., Cavalli, Trevisani, Comiti, & Marchi, 2013;Croke, Fryirs, & Thompson, 2013;Faulkner, 2008;Fryirs, Brierley, Preston, & Spencer, 2007;Fuller et al, 2016;Fuller & Marden, 2011;Harvey, 2001;Harvey, 2012;Heckmann & Schwanghart, 2013;Johnson, Warburton, & Mills, 2008;Jones & Preston, 2012;Kuo & Brierley, 2014;Mekonnen, Keesstra, Baartman, Stroosnijder, & Maroulis, 2016;Messenzehl, Hoffmann, & Dikau, 2014;Nicoll & Brierley, 2017;Warburton, 2009;Wethered, Ralph, Smith, Fryirs, & Heijnis, 2015). However, the broader impacts of catchment-scale sediment connectivity (as studied by geomorphologists) on the functioning of stream ecosystems have largely been overlooked, beyond an acknowledgement that high (i.e., exceeding transport capacity) sediment delivery is generally bad for stream health (e.g., Sandercock & Hooke, 2011;Waters, 1995).…”
Section: Aims and Rationalementioning
confidence: 99%